1981
DOI: 10.1111/j.1600-0765.1981.tb00950.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of blood flow in attached gingiva of dogs following brushing

Abstract: A 133Xenon clearance technique was used io measure blood flow in the capillary bed of non‐inflamed attached gingiva. Measurements were made before and after brushing in a standardized manner. The results show that blood flow through attached gingiva is greater than in published data for skin and increases significantly with brushing. The increases measured, however, are much smaller than those reported for skin under similar stimuli. It is concluded that the high flow within unbrushed attached gingiva may be n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…In the present study we intended to observe whether brushing with a new toothbrush, a daily and mandatory behavior, can produce significant changes in the vascular microdynamics of the marginal gingiva of adolescents. In addition to classical tests, periodontal probing depth and gingival index, we used laser Doppler flowmetry, knowing that this is a noninvasive, objective method that can identify changes in blood flow after brushing [ 2 , 3 ] in real time and before the occurrence of clinical signs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study we intended to observe whether brushing with a new toothbrush, a daily and mandatory behavior, can produce significant changes in the vascular microdynamics of the marginal gingiva of adolescents. In addition to classical tests, periodontal probing depth and gingival index, we used laser Doppler flowmetry, knowing that this is a noninvasive, objective method that can identify changes in blood flow after brushing [ 2 , 3 ] in real time and before the occurrence of clinical signs.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of tooth brushing on gingival blood flow has been a topic of interest for researchers, being studied in both animals and human subjects. In 1981, Nuki et al [ 2 ] performed a study on dogs and recorded the evolution of blood flow to the capillaries in the attached gingiva. For this purpose, they used measurements of the clearance of a diffusible isotope such as 133Xe, which are known to reflect changes in the blood flow rate in capillaries.…”
Section: Introductionmentioning
confidence: 99%
“…This, as well, may be due to the brushing force which varies in the different regions of the dental arch (Bjom & Lindhe 1966, Kakudo et al 1969, Heath & Wilson 1974, Mierau & Spindler 1984. Some authors (Nuki et al 1981, White 1983) have proposed that dental plaque can be removed more effectively by increasing the brushing force. According to our results such improved cleanness is achieved at the expense of gingival trauma.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of mechanical stimulation on gingival tissue has been shown to promote gingival keratinization, which may increase the defensive function of gingival tissue (Caffesse et al, 1982), The immediate effect of gingival stimulation on improvement of microcircuiatory function has also been investigated. Temperature in the attached and sulcular gingiva increased after toothbrush stimulation (Kroone et al, 1980), This finding suggested that dilation of the gingival microvasculature resulted in an increase in gingival blood flow, A small increase in gingival blood flow was found after stimulation of attached gingiva in dogs using the '-'"'Xe clearance method (Nuki et al, 1981),…”
mentioning
confidence: 99%